FROM REDUNDANCY TO CLARITY: ADDRESSING CIRCUMLOCUTION IN STUDENTS’ ENGLISH TRANSLATIONS - Karini, Zulia (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2025)
This study examines the phenomenon of circumlocution in Indonesian–English student translations. Circumlocution, defined as the unnecessary use of repetitive or wordy expressions, often appears when learners translate directly from Indonesian into English, producing texts that are redundant and less communicative. Using a descriptive qualitative approach, 20 translation samples from senior high school students were analyzed to identify types of circumlocution, propose revisions through sentence-combining strategies, and explain possible causes. Four major patterns were found: repetition of words, repetition of phrases, repetition of clauses, and verbose sentences. The analysis shows that circumlocution is influenced by limited vocabulary, transfer from Indonesian discourse norms, restricted syntactic repertoire, and the pressure of timed translation tasks. By reconstructing circumlocution into concise alternatives, this study provides insights into both translation pedagogy and EFL writing instruction. The findings emphasize the importance of training students in economy of expression to produce clearer and more natural English translations.